Catheter-Directed Thrombolysis for Postpartum Deep Venous Thrombosis - Girona, Miguel; Säly, Christoph; Makaloski, Vladimir; Baumgartner, Iris; Schindewolf, Marc (Frontiers in Cardiovascular Medicine, 2022)
Venous thromboembolism is a major concern during pregnancy as well as in the postpartum period. In acute proximal deep venous thrombosis, endovascular recanalization with locally administered thrombolytic agents has evolved as therapeutic alternative to anticoagulation alone. However, data on the bleeding risk of thrombolysis in the postpartum period is limited. We addressed the key clinical question of safety outcomes of catheter-directed thrombolysis (CDT) in the peri- and postpartum period. Therefore, we performed a non-exhaustive literature review and illustrated the delicate management of a patient with postpartum acute iliofemoral thrombosis treated with CDT and endovascular revascularization with thrombectomy, balloon angioplasty and stenting.